Amorphous lithium ion conductive oxide powder and its manufacturing method, and method for manufacturing lithium ion conductive oxide powder having NASICON type crystal structure

JP7644594B2Active Publication Date: 2025-03-12DOWA ELECTRONICS MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020209982
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-18
Publication Date
2025-03-12
Estimated Expiration
2040-12-18

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、結晶化することにより高いイオン伝導度を発揮するNASICON型結晶構造のリチウムイオン伝導酸化物粉末を得ることが出来るNASICON型結晶構造のリチウムイオン伝導酸化物粉末の前駆体である非晶質リチウムイオン伝導酸化物粉末と、当非晶質リチウムイオン伝導酸化物粉末を、安価な原料コストと生産コストによって製造する製造方法と、より高いイオン伝導度を発揮するNASICON型結晶構造を有するリチウムイオン伝導酸化物粉末の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644594000005
    Figure 0007644594000005
  • Figure 0007644594000006
    Figure 0007644594000006
  • Figure 0007644594000007
    Figure 0007644594000007
Patent Text Reader

Abstract

To provide: an amorphous lithium-ion-conducting oxide powder which, upon crystallization, becomes a lithium-ion-conducting oxide powder having a NASICON-type crystal structure and exhibits high ionic conductivity; a method for producing amorphous lithium-ion-conducting oxide powder with low raw material cost and production cost; and a lithium-ion-conducting oxide powder having a NASICON-type crystal structure that exhibits higher ionic conductivity.SOLUTION: An amorphous lithium-ion conducting oxide powder containing lithium in an amount of 0.5-6.5 mass%, aluminum in an amount of 0-25.0 mass%, germanium in an amount of more than 0 mass% and at most 65.0 mass%, phosphorus in an amount of 10-30 mass%, and carbon in an amount of more than 0 mass% and at most 0.35 mass%, and having a specific surface area of 15 m2 / g to 100 m2 / g as measured by the BET single point method.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an amorphous lithium ion conductive oxide powder, a method for producing the same, and a method for producing a lithium ion conductive oxide powder having a NASICON type crystal structure.

Background Art

[0002] As a material for the solid electrolyte of an all-solid-state battery, there is a lithium ion conductor having a NASICON type crystal structure with high ionic conductivity. One of them is a lithium ion conductor described by the general formula Li 1+x Al x Ge 2-x (PO4)3 (where the range of x is 0 < x ≤ 1) (which may be referred to as "LAGP" in the present invention) is known.

[0003] The NASICON type crystal structure is a crystal structure known to have a space group R3c and high lithium ion conductivity. Whether the measurement target is a NASICON type crystal structure can be determined by powder X-ray diffraction measurement. For example, in the case of LAGP described above, it can be identified by comparison with the JCPDS card No. 01-080-1922.

[0004] In order to obtain high ionic conductivity, a method is known in which amorphous LAGP as described in Patent Documents 1 and 2 is used, molded, and then fired and crystallized for a lithium ion conductor having a NASICON type crystal structure.

[0005] The following methods are known for producing amorphous LAGP. 1. A method for producing amorphous LAGP by a sol-gel method using metal alkoxide (see Patent Document 1). 2. A method for producing amorphous LAGP by a glass melting method (see paragraph (0018) of Patent Document 2).

Prior Art Documents

Patent Documents

[0006] [Patent Document 1] JP 2018-37341 A [Patent Document 2] JP 2018-101467 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, according to the study by the present inventors, even when a molded body is produced using amorphous LAGP produced by the method described in Patent Documents 1 and 2, and then the molded body is sintered to crystallize the LAGP, the ionic conductivity is low. Therefore, in order to further improve the output of all-solid-state batteries, the inventors have come to the conclusion that an amorphous lithium ion conductor is required that can be sintered and crystallized to become a lithium ion conductor with a NASICON type crystal structure that exhibits higher ionic conductivity.

[0008] Furthermore, the firing process described in Patent Document 1 requires the firing process to be performed in an inert atmosphere in order to prevent the generation of GeO2, a resistive component with no ion conductivity, in order to increase the ion conductivity, and this method increases raw material costs and production costs. In addition, the glass melting method described in Patent Document 2 also requires two types of LAGP, a first LAGP powder having a particle size of 2.1 μm to 2.5 μm and a second LAGP powder having a particle size of 0.18 μm to 0.25 μm, in order to increase ion conductivity, and is a method that increases raw material costs and production costs. In addition, it is necessary to melt the raw materials at high temperatures, and lithium and germanium, which are easily volatile elements, volatilize during melting, which causes a problem of composition deviation.

[0009] The present invention has been made under the above-mentioned circumstances, and the problem to be solved by the present invention is to provide an amorphous lithium ion conductive oxide powder, which is a precursor of a lithium ion conductive oxide powder with a NASICON type crystal structure that can be crystallized to obtain a lithium ion conductive oxide powder with a NASICON type crystal structure that exhibits high ionic conductivity; a manufacturing method for manufacturing the amorphous lithium ion conductive oxide powder at low raw material and production costs; and a manufacturing method for a lithium ion conductive oxide powder with a NASICON type crystal structure that exhibits higher ionic conductivity. [Means for solving the problem]

[0010] In order to solve the above-mentioned problems, the inventors discovered that an amorphous lithium ion conductive oxide powder containing predetermined amounts of the elements lithium, aluminum, germanium, and phosphorus, and having a carbon content and BET specific surface area within a predetermined range, can be obtained. When crystallized, this becomes a lithium ion conductive oxide powder with a NASICON crystal structure and exhibits high ionic conductivity.

[0011] Based on the above findings, the inventors have come up with a configuration in which a carbon-free inorganic compound is used as a raw material containing, in addition to the main constituent elements of the amorphous lithium ion conductive oxide powder, such as lithium, aluminum, germanium, and phosphorus, elements that substitute for the main constituent elements aluminum and germanium as desired, and elements such as phosphorus and silicon that are added as desired, and a configuration in which an aqueous solution of an inorganic compound containing the above-mentioned constituent elements is mixed, a slurry containing the constituent elements of the lithium ion conductor is spray-dried by a coprecipitation method, and the mixture is fired at a temperature of 300°C to 500°C, thereby solving the above-mentioned problems.

[0012] That is, the first invention for solving the above-mentioned problems is: Lithium, 0.5% by mass or more and 6.5% by mass or less; Aluminum, more than 0 mass% and 25.0 mass% or less, Germanium, more than 0 mass% and not more than 65.0 mass%; Contains 10% by mass or more and 30% by mass or less of phosphorus, The specific surface area measured by the BET single point method is 15 m 2 / g or more 100m 2 / g or less. The second invention is Lithium, 1% by mass or more and 4% by mass or less; Aluminum, more than 0 mass% and not more than 6 mass%; The amorphous lithium ion conductive oxide powder according to the first aspect of the present invention contains more than 15 mass % and not more than 35 mass % of germanium. The third invention is The amorphous lithium ion conductive oxide powder according to the first or second invention further contains 0.01% by mass or more and 0.35% by mass or less of carbon. The fourth invention is The specific surface area measured by the BET single point method is 20m 2 / g or more 100m 2 The amorphous lithium ion conductive oxide powder according to any one of the first to third aspects of the present invention has a molecular weight of 1.0 to 1.5 μm, and a molecular weight of 1.0 to 1.5 μm is 0.01 to 0.1 μm. The fifth invention is The amorphous lithium ion conductive oxide powder according to any one of the first to fourth aspects of the present invention further contains at least one element selected from titanium, zirconium and hafnium. The sixth invention is The amorphous lithium ion conductive oxide powder according to any one of the first to fifth aspects of the present invention further contains 10 mass % or less of silicon. The seventh invention is The amorphous lithium ion conductive oxide powder has the general formula Li 1+x+w (Al 1-y M1 y ) x (Ge 1-z M2 z ) 2-x P 3-w S w O 12It is represented by the formula, M1 is one or more selected from gallium, lanthanum, indium and yttrium, M2 is one or more selected from titanium, zirconium and hafnium, the range of x is 0 < x ≤ 1.0, the range of y is 0 ≤ y ≤ 1.0, the range of z is 0 ≤ z ≤ 1.0, and the range of w is 0 ≤ w ≤ 1.0. It is an amorphous lithium ion conductive oxide powder according to any one of the first to sixth inventions. The eighth invention is Furthermore, it is an amorphous lithium ion conductive oxide powder according to any one of the first to sixth inventions, containing at least one element selected from gallium, lanthanum, indium and yttrium. The ninth invention is An aqueous solution of a lithium compound, aluminum D An aqueous solution of a um compound, an aqueous solution of a germanium compound, and an aqueous solution of an ammonium phosphate salt are mixed to obtain a slurry forming step of a suspension of a coprecipitate, A step of spray-drying the slurry to obtain a slurry dried product, And a step of firing the slurry dried product at 300 or more and 500 or less. It is a method for producing an amorphous lithium ion conductive oxide powder. The tenth invention is In the slurry forming step, an aqueous solution of a compound containing at least one element selected from gallium, lanthanum, indium and yttrium is further mixed to obtain a suspension of a coprecipitate. It is a method for producing an amorphous lithium ion conductive oxide powder according to the ninth invention. The eleventh invention is In the slurry forming step, an aqueous solution of a compound containing at least one element selected from titanium, zirconium and hafnium is further mixed to obtain a suspension of a coprecipitate. It is a method for producing an amorphous lithium ion conductive oxide powder according to the ninth or tenth invention. The twelfth invention is In the slurry forming step, an aqueous solution of a silicon compound is further mixed to obtain a suspension of a coprecipitate It is a method for producing an amorphous lithium ion conductive oxide powder according to any one of the ninth to eleventh inventions. The thirteenth invention is This is a method for producing an amorphous lithium ion conductive oxide powder according to any one of the 9th to 12th aspects of the present invention, wherein the formation of the suspension in the slurry formation step is carried out by mixing an aqueous solution of the germanium compound adjusted to a pH of 8 or higher. The fourteenth invention is A method for producing a lithium ion conductive oxide powder having a NASICON type crystal structure, comprising the step of firing the amorphous lithium ion conductive oxide powder according to any one of the first to eighth aspects of the present invention at a temperature higher than 500°C. The fifteenth invention is Aqueous solution of lithium compounds and aluminum D a slurry formation step of mixing an aqueous solution of an ammonium compound, an aqueous solution of a germanium compound, and an aqueous solution of an ammonium phosphate salt to obtain a coprecipitate suspension; A step of spray-drying the slurry to obtain a dried slurry; and calcining the dried slurry at a temperature higher than 500°C. Effect of the Invention

[0013] According to the present invention, it is possible to provide an amorphous lithium ion conductive oxide powder, which is a precursor of a lithium ion conductive oxide powder with a NASICON type crystal structure, which can be crystallized to obtain a lithium ion conductive oxide powder with a NASICON type crystal structure that exhibits high ionic conductivity; a manufacturing method for manufacturing the amorphous lithium ion conductive oxide powder at low raw material and production costs; and a manufacturing method for a lithium ion conductive oxide powder with a NASICON type crystal structure that exhibits higher ionic conductivity. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a flow diagram showing a manufacturing process of the lithium ion conductive oxide powder according to the present invention. [Diagram 2]SEM photographs of the lithium ion conductive oxide powder according to Example 1, Comparative Examples 1 and 2, magnified 30,000 times. [Diagram 3] XRD spectrum of the amorphous lithium ion conductive oxide powder according to Example 1. [Figure 4] XRD spectrum of the lithium ion conductive oxide powder having a NASICON type crystal structure according to Example 1. [Diagram 5] Flow chart showing the manufacturing process of the lithium ion conductive oxide powder according to Comparative Example 1. [Figure 6] Flow chart showing the manufacturing process of the lithium ion conductive oxide powder according to Comparative Example 2.

BEST MODE FOR CARRYING OUT THE INVENTION

[0015] The amorphous lithium ion conductive oxide powder according to the present invention is a precursor that can obtain a lithium ion conductive oxide powder having a NASICON type crystal structure by firing and crystallization. The amorphous lithium ion conductive oxide powder and the lithium ion conductive oxide powder having a NASICON type crystal structure according to the present invention are represented by, for example, the general formula Li 1+x+w (Al 1-y M1 y ) x (Ge 1-z M2 z ) 2-x P 3-w Si w O 12 (wherein M1 is at least one selected from gallium, lanthanum, indium and yttrium, M2 is at least one selected from titanium, zirconium and hafnium, the range of x is 0 < x ≦ 1.0, the range of y is 0 ≦ y ≦ 1.0, the range of z is 0 ≦ z ≦ 1.0, and the range of w is 0 ≦ w ≦ 1.0). The amorphous lithium ion conductive oxide powder according to the present invention is molded into, for example, a pellet or sheet, and then the molded product is fired and crystallized to produce a fired body of lithium ion conductive oxide powder having a NASICON crystal structure. The fired body of lithium ion conductive oxide powder having a NASICON crystal structure is used as a solid electrolyte in an all-solid-state battery. The lithium ion conductive oxide powder and its manufacturing method according to the present invention, as well as the manufacturing method of lithium ion conductive oxide powder having a NASICON type crystal structure, will be described below in the order of [1] constituent elements, [2] BET specific surface area, and [3] manufacturing method.

[0016] [1] Constituent elements The amorphous lithium ion conductive oxide powder according to the present invention contains at least lithium, aluminum, germanium, and phosphorus as constituent elements. + It is an element that provides carriers and brings about lithium ion conduction. Aluminum substitutes for germanium, a tetravalent metal element described later, and acts as a charge compensator. + It is a trivalent element added to increase the number of carriers. Germanium is a tetravalent metal element necessary for the lithium ion conductive oxide powder to have a NASICON type crystal structure when crystallized, and phosphorus is a pentavalent metal element necessary for the lithium ion conductive oxide powder to have a NASICON type crystal structure when crystallized.

[0017] In addition, the above-mentioned constituent elements, aluminum and germanium, may be partially substituted with other elements. Aluminum may be partially substituted with one or more elements selected from gallium, lanthanum, indium, and yttrium. Germanium may be partially substituted with one or more elements selected from titanium, zirconium, and hafnium.

[0018] Phosphorus can be partially replaced by silicon. By replacing the pentavalent phosphorus with the tetravalent silicon, Li +This makes it possible to increase the number of carriers, which can contribute to improving Li-ion conductivity.

[0019] Here, the content ratio of the main constituent substances will be described. The lithium content is 0.5% by mass or more and 6.5% by mass or less as lithium element. This is because if the lithium content is 0.5 mass% or more, lithium ion conductivity is ensured. On the other hand, if the lithium content is 6.5 mass% or less, the lithium ion conductive oxide powder becomes NASICON when crystallized. Type crystal The lithium content is preferably 1.0 mass% or more, more preferably 1.5 mass% or more, and even more preferably 1.8 mass% or more, and on the other hand, is preferably 4.0 mass% or less, preferably 3.5 mass% or less, and even more preferably 3.3 mass% or less.

[0020] The aluminum content, as elemental aluminum, is more than 0 mass % and 25.0 mass % or less. This is because the addition of aluminum can improve the lithium ion conductivity in the lithium ion conductive oxide powder having a NASICON type crystal structure. If the aluminum content is 25.0 mass% or less, the lithium ion conductive oxide powder will have a NASICON type crystal structure when crystallized. The aluminum content is preferably 0.5 mass% or more, more preferably 1.0 mass% or more, and preferably 6.0 mass% or less, while more preferably 5.5 mass% or less, and even more preferably 5.0 mass% or less.

[0021] The germanium content is more than 0 mass % and 65.0 mass % or less as elemental germanium. If the germanium content exceeds 0% by mass, it can form glass and become amorphous. On the other hand, if the germanium content is 65.0% by mass or less, the lithium ion conductive oxide powder will have a NASICON type crystal structure when crystallized. The germanium content is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 22% by mass or more, while it is preferably 35% by mass or less, more preferably 33% by mass or less, and even more preferably 30% by mass or less.

[0022] In the amorphous lithium ion conductive oxide powder according to the present invention, phosphorus is contained in an amount of 10% by mass or more and 30% by mass or less as phosphorus element. In this case, glass can be formed and the powder can be made amorphous. Meanwhile, when crystallized, the lithium ion conductive oxide powder has a NASICON type crystal structure. The phosphorus content is preferably 15% by mass or more, more preferably 20% by mass or more, while it is preferably 28% by mass or less, more preferably 25% by mass or less.

[0023] The content (mass %) of each element in the amorphous lithium ion conductive oxide powder according to the present invention described above is the value of the quantitative analysis result of each constituent element obtained by preparing a solution by alkali-melting the amorphous lithium ion conductive oxide powder and quantitatively analyzing each constituent element of this solution using an emission spectrometer (ICP-720 manufactured by Agilent).

[0024] In the amorphous lithium ion conductive oxide powder according to the present invention, the carbon content is preferably 0.35% by mass or less. By making the carbon content 0.35% by mass or less, it is possible to suppress the carbon from burning during firing for crystallization, which causes pores to form in the burned portion and leads to a deterioration in ion conductivity. The amorphous lithium ion conductive oxide powder can have a carbon content of, for example, 0.01% by mass or more and 0.35% by mass or less. The carbon content is preferably 0.3% by mass or less, more preferably 0.25% by mass or less. The method for measuring the carbon content will be explained in the Examples.

[0025] In the amorphous lithium ion conductive oxide powder according to the present invention, the total content of the lithium element, aluminum element, germanium element, the above-mentioned substitution metal element added as required, phosphorus element, carbon, and oxygen is 90.0 mass% or more and 100.0 mass% or less, and more preferably 95.0 mass% or more, with the remainder being impurities.

[0026] On the other hand, the amount of oxygen in the amorphous lithium ion conductive oxide powder according to the present invention was calculated based on the fact that each metal element and phosphorus are oxides and the amount of each metal element and phosphorus measured by ICP analysis. The amount of oxygen in the amorphous lithium ion conductive oxide powder is preferably 25 to 60 mass%. The amount of impurities was calculated by subtracting the amount of each metal element, phosphorus, carbon, and oxygen from 100 mass%. A specific example of the calculation will be described in the Examples.

[0027] The amorphous lithium ion conductive oxide powder according to the present invention may further contain 10% by mass or less of silicon. The addition of silicon makes it easier to form glass. If the amount of silicon added exceeds 10% by mass, the lithium ion conductive oxide powder cannot have a NASICON type crystal structure when crystallized, which results in a deterioration of ion conductivity. The silicon content is preferably 5% by mass or less, more preferably 3% by mass or less.

[0028] When the amorphous lithium ion conductive oxide powder of the present invention contains silicon, the total content of lithium, aluminum, germanium, phosphorus, carbon, oxygen, and silicon atoms is 90.0 mass% or more and 100.0 mass% or less, and it is more preferable that it is 95.0 mass% or more.

[0029] On the other hand, the amorphous lithium ion conductive oxide powder according to the present invention may contain about 10% by mass, preferably about 3.0% by mass of impurities other than lithium, aluminum, germanium, the above-mentioned substitution metal elements added as required, phosphorus, carbon, and oxygen. The impurities are zirconia and the like of the beads used in producing the amorphous lithium ion conductive oxide powder. a However, this level of content does not have any adverse effect on the lithium ion conductive properties when a lithium ion conductor having a NASICON crystal structure is formed.

[0030] [2] BET specific surface area The amorphous lithium ion conductive oxide powder according to the present invention has a BET specific surface area of ​​15 m 2 / g or more 100m 2 / g or less. 2 / g or more 100m 2 When the lithium ion conductive oxide powder has a BET specific surface area of ​​20 m / g or less, heat is applied uniformly to the lithium ion conductive particles contained therein when the lithium ion conductive oxide powder is sintered, and crystallization occurs uniformly throughout the particles, improving the ion conductivity. 2 / g or more, more preferably 22m 2 / g or more, preferably 80m 2 / g or less, more preferably 60m 2 / g or less. A specific method for measuring the BET specific surface area will be described in the Examples.

[0031] [3] Manufacturing method The amorphous lithium ion conductive oxide powder according to the present invention and a method for producing the lithium ion conductive oxide powder having a NASICON type crystal structure will now be described. To produce the amorphous lithium ion conductive oxide powder according to the present invention and the lithium ion conductive oxide powder having a NASICON crystal structure, first, the raw materials containing each constituent element are completely dissolved in water to obtain an aqueous solution, and each constituent element is made into an ion state. The aqueous solutions of each constituent element are mixed, and each constituent element is precipitated to obtain a slurry. The obtained slurry is spray-dried to obtain a powder, and then fired to obtain a fired product, which is then pulverized. When generating a precipitate from the aqueous solution in which each constituent element is dissolved, acidic solutions and alkaline solutions may be mixed together in advance.

[0032] Hereinafter, the amorphous lithium ion conductive oxide powder according to the present invention and the method for producing the lithium ion conductive oxide powder having a NASICON type crystal structure will be described with reference to FIG. 1, which is a flow chart showing the steps of producing the amorphous lithium ion conductive oxide powder, including (1) preparation of raw material aqueous solution, (2) mixing, and (3) spraying. Drying (4) calcination, (5) crushing, (6) drying, (7) sintering, and (8) preparation of lithium ion conductive oxide powder having a NASICON-type crystal structure will be described in that order.

[0033] (1) Preparation of raw material aqueous solution The raw materials containing the constituent elements of the lithium ion conductive oxide powder according to the present invention, lithium, aluminum, germanium, phosphorus, and optionally the substituting elements for aluminum and germanium, and the additive elements phosphorus and silicon, are each completely dissolved in water to obtain an aqueous solution. In this case, if the raw materials are water-soluble salts not containing carbon or elements that dissolve in a liquid, the oxides of the elements may be dissolved by adding an acid or an alkali.

[0034] On the other hand, when a raw material containing carbon, such as an acetate or an organic acid salt of each element, is used, there is a possibility that the carbon will remain in the lithium ion conductive oxide powder according to the present invention. From this viewpoint, it is preferable that the raw material containing each constituent element is an inorganic compound.

[0035] From the above, examples of raw material compounds of each element suitable for preparing the raw material aqueous solution are shown in Table 1. In this case, in Table 1, if the aqueous solution after dissolution has an acidic pH, the acidic raw material aqueous solutions may be mixed together. In addition, other raw material powders may be further added to and dissolved in the acidic raw material aqueous solution. The same applies to the case of mixing alkaline raw material aqueous solutions.

[0036] For example, when the raw material compound is germanium dioxide, germanium dioxide can be added to pure water and stirred while adding alkali to prepare a germanium aqueous solution. In this case, there is no need to consider the temperature during dissolution, and it does not matter whether the solution is heated or not. This is because germanium dioxide dissolves in an aqueous solution with a pH value in the range of about 8 to 12.

[0037] When using a raw material compound that is not water-soluble, the liquid property of the solution is adjusted, and it is preferable to use ammonia, which does not contain impurities, as the alkali. Nitric acid, sulfuric acid, hydrochloric acid, etc. can be used as the acid. In addition, an aqueous solution of lithium hydroxide can also be used as the alkali. In that case, the lithium hydroxide is of course weighed and used as a raw material compound for lithium.

[0038] [Table 1]

[0039] (2) Mixing (slurrying) This is a process in which the raw material aqueous solutions prepared in (1) above are mixed according to the composition of the desired lithium ion conductive oxide powder, and a slurry containing the constituent elements of the lithium ion conductor is obtained by coprecipitation. For example, when an acidic aqueous solution in which lithium nitrate, aluminum nitrate nonahydrate, and ammonium dihydrogen phosphate are dissolved is added to an alkaline aqueous solution of germanium dissolved in ammonia, the solution becomes cloudy immediately, and lithium, aluminum, germanium, and RIt is possible to obtain a slurry containing cations and the like. In this mixing step, there is no need to consider the liquid temperature, and it may be heated or not. It is considered that the slurry contains constituent elements that have precipitated as hydroxides and constituent elements that exist as ions. In order to reduce the amount of carbon derived from carbon dioxide in the slurry, it is also preferable to purge the slurry with nitrogen.

[0040] In the present invention, the raw material aqueous solutions are mixed and a slurry containing the constituent elements of the lithium ion conductor is obtained by the coprecipitation method in order to realize a supersaturated state in which the ion concentration product of the constituent elements in the mixed solution is higher than the solubility product by adopting the coprecipitation method. By realizing the supersaturated state, the number of nuclei of the precipitates generated increases, and as a result, the particle size of the precipitates decreases, and finally, the effect of increasing the BET specific surface area of ​​the particles of the amorphous lithium ion conductor can be obtained. It is considered that not all of the constituent elements of the lithium ion conductor can be precipitated in the coprecipitation method in the present invention, but most of the constituent elements are coprecipitated, and the effect of improving the uniformity of the constituent elements in the particles of the amorphous lithium ion conductor can be obtained.

[0041] In contrast, when dehydration is performed from a raw solution in which the constituent elements are completely dissolved, precipitation occurs due to a change in solubility, and not due to sudden supersaturation caused by a change in pH as in the coprecipitation method described above. Condition As a result, the number of nuclei of the precipitates produced decreases, and the particle size of the precipitates increases. Furthermore, since the solubility of the constituent elements differs, the constituent elements with low solubility will precipitate first during the dehydration process, and the constituent elements with high solubility will precipitate later, which may result in non-uniformity of the particles produced.

[0042] (3) Spray drying This is a step in which the slurry obtained in (2) above is spray-dried using a spray dryer or the like to evaporate the water in the slurry and obtain a powder. The drying step is provided because, although most of the constituent elements lithium, aluminum, germanium, and phosphorus, and the above-mentioned substitution metal elements added as desired, are coprecipitated in the slurry obtained in (2) above, some elements are present as ions. For example, it is considered that a lithium ion conductor having the intended composition cannot be obtained if the powder recovered from the slurry by the filtration step is used.

[0043] On the other hand, it is possible to obtain a powder from the obtained slurry by evaporating to dryness using a hot plate or the like, instead of spray drying. However, if the dehydration time is long, there is a risk that the constituent elements existing as ions in the slurry will precipitate non-uniformly due to the difference in solubility between the constituent elements. Here, by carrying out dehydration as quickly as possible, it is possible to reduce the non-uniformity of precipitation caused by the difference in solubility between the constituent elements. Therefore, it is believed that the spray drying method is more effective in achieving uniformity in the composition of the particles than methods such as evaporation to dryness. Furthermore, from the viewpoint of production, the spray drying method is preferable because it can remove the solvent in a short time.

[0044] By carrying out spray drying, the elements contained in the slurry remain in the dried powder, but the obtained dried powder can be calcined to volatilize and remove excess impurities by heat. In addition, in order to remove impurities, a process of washing the dried powder with water to remove impurities and drying may be added.

[0045] (4) Firing This is a process in which the powder obtained in the above (3) is fired to remove ammonia and nitric acid components derived from the raw materials remaining in the powder to obtain an amorphous lithium ion conductive oxide powder, or a lithium ion conductive oxide powder having a NASICON type crystal structure is obtained without going through the amorphous lithium ion conductive oxide powder. Below, the steps for (I) obtaining an amorphous lithium ion conductive oxide powder and (II) obtaining a lithium ion conductive oxide powder having a NASICON type crystal structure are described.

[0046] (I) To obtain amorphous lithium ion conductive oxide powder As described above, a dense compact can be obtained by compressing and sintering amorphous lithium ion conductive powder, but if impurities such as ammonia and nitric acid components are present in the amorphous lithium ion conductive oxide powder and sintering is performed while the impurities are still present, the impurities may burn or volatilize, causing pores in the impurities and making it impossible to obtain a dense pellet. Therefore, the amorphous lithium ion conductive oxide powder is sintered at a temperature of 500°C or less.

[0047] Specifically, the amorphous lithium ion conductor powder obtained in (3) above is placed in a container made of alumina or the like, and the temperature is increased from room temperature to 300°C to 500°C at a rate of 0.1 to 20°C / min. By firing at 300°C or higher, it becomes easier to remove ammonia, nitric acid components, etc., while by setting the temperature at 500°C or lower, crystallization of the lithium ion conductor can be avoided. Then, amorphous lithium ion conductive oxide powder is obtained by firing for 60 to 180 minutes after the temperature reaches 300° C. to 500° C. The firing atmosphere is not limited to an air atmosphere and may be a nitrogen atmosphere, but an air atmosphere is preferable from the viewpoint of cost and productivity, and a nitrogen atmosphere is preferable from the viewpoint of suppressing the production of lithium carbonate.

[0048] (II) To obtain lithium ion conductive oxide powder having a NASICON type crystal structure Specifically, as described above, the amorphous lithium ion conductive oxide powder obtained in (3) is placed in a container made of alumina or the like, and is calcined at a temperature exceeding 500°C, preferably 550°C to 900°C, to obtain a lithium ion conductive oxide powder having a NASICON crystal structure, thereby obtaining a lithium ion conductive oxide powder having a NASICON crystal structure. The heating rate is not particularly limited, but is preferably 1 to 20°C / min. There is no particular restriction on the calcination atmosphere, but it is preferably an air atmosphere. The calcination time is not particularly limited, but is preferably 30 minutes to 300 minutes after the temperature exceeds 500°C and reaches 900°C or less.

[0049] (5) Crushing This is a step of pulverizing the amorphous lithium ion conductive oxide powder obtained in the above (4) to a particle size required for a subsequent step. The particle size of the amorphous lithium ion conductive oxide powder does not affect the ion conductivity. However, for example, when forming the lithium ion conductive oxide powder into a sheet, it is not preferable for particles to be present that are larger than the desired sheet thickness, and it is necessary to adjust the particle size. As a pulverization method, although known methods can be used, wet pulverization using a bead mill or the like is preferable. When wet pulverization is performed, solid-liquid separation is performed after the treatment, and the lithium ion conductive oxide powder is dried. For example, a preferable particle size of the amorphous lithium ion conductive oxide powder is a cumulative 50% particle size (D 50 ) is 1 μm to 5 μm.

[0050] The solvent used in wet grinding is preferably an organic solvent, specifically IPA, because IPA volatilizes during drying after grinding and does not remain in the lithium ion conductive oxide powder. When the solvent is water, lithium undergoes ion exchange with protons, which may lead to a deterioration in lithium ion conductivity. When a bead mill is used for pulverization, zirconia beads are preferred. By going through the above steps (1) to (5), the amorphous lithium ion conductive oxide powder according to the present invention can be obtained.

[0051] (6) Drying When the amorphous lithium ion conductive oxide powder is subjected to wet grinding in the step (5), it is then subjected to solid-liquid separation such as filtration, and dried at a temperature range that is equal to or higher than the boiling point of the solvent used and equal to or lower than the firing temperature in the step (4) to remove the solvent used, thereby obtaining the lithium ion conductive oxide powder according to the present invention. However, when the lithium ion conductive oxide powder is subjected to dry pulverization in the above step (5), the lithium ion conductive oxide powder according to the present invention can be obtained even if the drying step is omitted.

[0052] Whether the lithium ion conductive oxide powder is amorphous can be confirmed by observing a halo in the region of 2θ: 15° to 40° by powder X-ray diffraction (XRD) measurement. Note that a "halo" is a gentle fluctuation in X-ray intensity, and is observed as a broad rise in an X-ray chart. The half-width of the halo is 2θ: 2° or more.

[0053] (7) Firing The amorphous lithium ion conductive oxide powder obtained in the above (6) is fired and crystallized to produce a lithium ion conductive oxide powder having a NASICON type crystal structure. The firing temperature is more than 500°C, and preferably 550°C or higher and 900°C or lower. There is no particular limitation on the firing atmosphere, but an air atmosphere is preferred. The firing time is not particularly limited, but it is preferable to set the firing time from exceeding 500° C. to reaching 900° C. or less, for 30 minutes or more and 300 minutes or less.

[0054] (8) Lithium ion conductive oxide powder with NASICON type crystal structure By the steps described above, a lithium ion conductive oxide powder having a NASICON type crystal structure can be produced. The lithium ion conductive oxide powder having a NASICON type crystal structure contains the same elements as those contained in the amorphous lithium ion conductive oxide powder before crystallization described above. The lithium ion conductor of the present invention having the NASICON crystal structure was measured using an XRD device to obtain an XRD profile. The obtained XRD profile was compared with the JCPDS card No. 01-080-1922 using a computer attached to the XRD device to identify the crystal structure. EXAMPLES

[0055] Example 1 According to the flow chart showing the manufacturing process of the amorphous lithium ion conductive oxide powder described above, the amorphous lithium ion conductive oxide powder according to Example 1 was manufactured. Then, the manufactured amorphous lithium ion conductive oxide powder according to Example 1 was analyzed and its characteristics were evaluated.

[0056] (1) Preparation of raw material aqueous solution In Example 1, (I) an alkaline germanium aqueous solution and (II) an acidic lithium, aluminum and phosphorus-containing aqueous solution were prepared as raw aqueous solutions. Each will be described below.

[0057] (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium oxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0058] (II) Aqueous solution containing lithium, aluminum, and phosphorus 21.7g of lithium nitrate, 39.4g of aluminum nitrate nonahydrate, and 72.5g of ammonium dihydrogen phosphate were added to 150g of pure water to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus thus prepared was 1.4, which means it was acidic.

[0059] (2) Mixing (slurrying) 720 g of the alkaline germanium aqueous solution was taken and heated to 40° C. with stirring, and the entire amount (283.7 g) of the acidic lithium, aluminum, and phosphorus-containing aqueous solution was added thereto. Ta Immediately after the addition, the aqueous solution became cloudy and a white slurry was obtained, the pH value of which was 4.3.

[0060] (3) Spray drying The white slurry was spray-dried using a spray dryer (SD-1000 manufactured by Tokyo Rikakikai Co., Ltd.) to evaporate the water in the white slurry and precipitate it in a solid phase at once, thereby obtaining a white powder. The spray-drying conditions were an inlet temperature of 180°C, an outlet temperature of 90°C, and a white slurry addition rate of 10 g / min.

[0061] (4) Firing The white powder obtained by the spray drying was placed in an alumina container, and the temperature was increased from room temperature to 400°C at a rate of 5°C / min. After reaching 400°C, the powder was fired in an air atmosphere for 120 minutes to obtain an amorphous lithium ion conductive oxide powder. A SEM photograph of the obtained amorphous lithium ion conductive oxide powder at 30,000 times magnification is shown in FIG. 2 (Example 1).

[0062] (5) Wet grinding 40 g of the amorphous lithium ion conductive oxide powder was loaded into a bead mill together with 160 g of φ1 mm Zr beads and 94.32 g of IPA, and wet-milled for 120 minutes to adjust the particle size, thereby obtaining an amorphous lithium ion conductive oxide powder with adjusted particle size.

[0063] (6) Drying The amorphous lithium ion conductive oxide powder with the adjusted particle size was placed in a dryer and dried at 100° C. for 3 hours, and the IPA was removed to obtain the amorphous lithium ion conductive oxide powder according to Example 1. The volume-based cumulative 50% particle diameter (D 50 ) was measured with Helos (dispersion pressure 5 bar) to be 1.8 μm. This value is shown in Table 3.

[0064] (7) Amorphous lithium ion conductive oxide powder The following were carried out on the obtained amorphous lithium ion conductive oxide powder: (I) composition analysis, (II) carbon content analysis, (III) oxygen content calculation, (IV) BET specific surface area measurement, (V) XRD measurement of the amorphous lithium ion conductive oxide powder, (VI) ionic conductivity evaluation, and (VII) XRD measurement of the pressed and sintered body of the lithium ion conductor. Each method and result is explained below.

[0065] (I) Composition analysis The amorphous lithium ion conductive oxide powder according to Example 1 was dissolved in an alkali using sodium carbonate as a melting agent. Then, the solution was subjected to elemental analysis using an ICP device (ICP-720 manufactured by Agilent), and the following were obtained: lithium: 2.43 mass%, aluminum: 3.02 mass%, germanium: 25.1 mass%, and phosphorus: 21.7 mass%. The analytical values ​​of each constituent element are shown in Table 2.

[0066] (II) Carbon content analysis The carbon content in the amorphous lithium ion conductive oxide powder according to Example 1 was measured using a trace carbon / sulfur analyzer (EMIA-U510 manufactured by Horiba, Ltd.) and found to be 0.16% by mass. This value is shown in Table 2.

[0067] (III) Oxygen Calculation The amount of oxygen in the amorphous lithium ion conductive oxide powder was calculated as follows. Since the oxide of monovalent lithium is Li2O, the amount of oxygen related to lithium oxide is expressed by the following formula. Amount of oxygen related to lithium oxide = (Li concentration × (formula weight of Li2O / number of Li atoms in Li2O) ÷ formula weight of Li) - Li concentration (formula) On the other hand, from the above (I), the ICP analysis result of the lithium concentration is 2.43 mass%, so Amount of oxygen related to lithium oxide = (2.43 x (29.88 / 2) ÷ 6.94) - 2.43 = 2.80 mass% It becomes.

[0068] Since the oxide of trivalent aluminum is Al2O3, the amount of oxygen related to aluminum oxide is expressed by the following formula. Amount of oxygen related to aluminum oxide = (Al concentration × (formula weight of Al2O3 / number of Al atoms in Al2O3) ÷ formula weight of Al) - Al concentration... (formula) On the other hand, the ICP analysis result for the aluminum concentration was 3.02 mass%, Amount of oxygen related to aluminum oxide = (3.02 x (101.96 / 2) ÷ 26.98) - 3.02 = 2.69 mass% It becomes.

[0069] Since the oxide of tetravalent germanium is GeO2, the amount of oxygen related to germanium oxide is expressed by the following formula. Amount of oxygen in germanium oxide = (Ge concentration × (formula weight of GeO2 / number of Ge atoms in GeO2) ÷ formula weight of Ge) - Ge concentration... (formula) On the other hand, the ICP analysis result for the germanium concentration was 25.1 mass%, Amount of oxygen related to germanium oxide = (25.1 x (104.61 / 1) ÷ 72.61) - 25.1 = 11.06 mass% It becomes.

[0070] Since the oxide of pentavalent phosphorus is P2O5, the amount of oxygen associated with phosphorus oxide can be expressed by the following formula. Amount of oxygen related to phosphorus oxide = (P concentration × (formula weight of P2O5 / number of P atoms in P2O5) ÷ formula weight of P) - P concentration (formula) On the other hand, the ICP analysis result for phosphorus concentration was 21.7 mass%, Amount of oxygen related to phosphorus oxide = (21.7 x (141.94 / 2) ÷ 30.97) - 21.7 = 28.02 mass% It becomes.

[0071] From the above calculation results, the total amount of oxygen related to each metal element oxide and phosphorus oxide was 2.80+2.69+11.06+28.02=44.6 mass %. This value is shown in Table 2. The obtained amorphous lithium ion conductive oxide powder was Li1.5 Al 0.5 Ge 1.5 P 3.0 O 12 It was. Furthermore, from the amounts of the above-mentioned metal elements, phosphorus, carbon, and oxygen, the amount of impurities was calculated to be 3.0 mass %. This value is shown in Table 2.

[0072] (IV) BET specific surface area measurement The BET specific surface area of ​​the amorphous lithium ion conductive oxide powder according to Example 1 was measured using a BET specific surface area measuring device (Macsorb manufactured by Mountec Co., Ltd.). After degassing by flowing nitrogen gas into the measuring device for 20 minutes at 105° C., the BET specific surface area of ​​the amorphous lithium ion conductive oxide powder according to Example 1 was measured by the BET single point method while flowing a mixed gas of nitrogen and helium (N2: 30 vol %, He: 70 vol %). The result was 27.7 m 2 / g. This value is shown in Table 3.

[0073] (V) XRD Measurement of Amorphous Lithium Ion Conductive Oxide Powder XRD measurement was carried out on the amorphous lithium ion conductive oxide powder according to Example 1. The measurement conditions are shown in Table 4, and the obtained XRD spectrum is shown in FIG. From FIG. 3, it was confirmed that the lithium ion conductor according to Example 1 had an amorphous structure. This is shown in Table 3. This is because a halo was observed in the region of 2θ: 15° to 40° by XRD measurement. Note that a "halo" is a gentle fluctuation in X-ray intensity, and is observed as a broad rise in an X-ray chart. The half-width of the halo was 2θ: 2° or more.

[0074] (VI) Ionic conductivity evaluation 0.5 g of the amorphous lithium ion conductive oxide powder according to Example 1 was placed in a cylindrical insulating container having a diameter of 10 mm, and pressed together with a stainless steel current collector at 360 MPa using a press to obtain a green compact. The obtained compressed powder of amorphous lithium ion conductive oxide powder was sintered for 120 minutes after the furnace temperature reached 700°C, and crystallized to obtain lithium ion conductive oxide powder (Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12) A pressed powder sintered body was produced.

[0075] The pressed and sintered body of the lithium ion conductive oxide powder having a NASICON type crystal structure produced by the above sintering was measured in an air atmosphere at a temperature of 25°C using a potentio / galvanostat (1470E manufactured by Solartron) and a frequency response analyzer (1255B manufactured by Solartron) by the AC impedance method in the range of 100Hz to 4MHz. The resistance value of the pressed and sintered body having a NASICON type crystal structure was obtained from a Cole-Cole plot (complex impedance plane plot) of the measured value, and the ionic conductivity of the lithium ion conductive oxide powder having a NASICON type crystal structure, which was obtained by crystallizing the amorphous lithium ion conductive oxide powder, was calculated from the obtained resistance value, and was 6.4 x 10 -5 The values ​​are shown in Table 3.

[0076] (VII) XRD Measurement of Powder-Sintered Lithium Ion Conductor The pressed powder sintered body of the lithium ion conductor crystallized by sintering at 700°C for 120 minutes was subjected to XRD measurement under the conditions described in "(V) XRD measurement of amorphous lithium ion conductive oxide powder" above, and when the measurement was compared with JCPDS card No. 01-080-1922, a crystal peak of LAGP, a lithium ion conductor with a NASICON crystal structure, was observed, and it was found that the pressed powder sintered body of the lithium ion conductive oxide powder of Example 1 is a lithium ion conductor with a NASICON crystal structure. The obtained XRD spectrum is shown in Figure 4.

[0077] (Examples 2 to 8) The amorphous lithium ion conductive oxide powders of Examples 2 to 8 were produced by carrying out the same operations as in Example 1, except that the steps of "(1) Preparation of raw material aqueous solution" and "(2) Mixing (slurrying)" described in Example 1 were changed as described below. The amorphous lithium ion conductive oxide powders produced according to Examples 2 to 8 were used to carry out the steps (I) composition analysis, (II) carbon content analysis, (III) oxygen content analysis, (IV) BET specific surface area measurement, (V) XRD measurement of the amorphous lithium ion conductive oxide powder, (VI) ionic conductivity evaluation, and (VII) XRD measurement of the pressed and sintered body of the lithium ion conductor, as described in “(7) Amorphous lithium ion conductive oxide powder” of Example 1.

[0078] The results of the composition analysis of each constituent element in the amorphous lithium ion conductive oxide powders according to Examples 2 to 8 are shown in Table 2, including the oxygen content, carbon content, and impurity content. The cumulative 50% particle diameter (D 50 ) measured by Helos (dispersion pressure 5 bar), the crystal phase, and the BET specific surface area are shown in Table 3. The ionic conductivity of the lithium ion conductive oxide powder having the NASICON type crystal structure according to Examples 2 to 8 is also shown in Table 3. The method of calculating the oxygen amount of Ti, Zr, and Si contained in the amorphous lithium ion conductive oxide powder of Examples 5 to 7 will be described in each Example. In Examples 5 to 7, the method of calculating the oxygen amount of elements other than Ti, Zr, and Si is the same as in Example 1.

[0079] Example 2 (1) Preparation of raw material aqueous solution (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium dioxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0080] (II) Aqueous solution containing lithium, aluminum, and phosphorus To 150 g of pure water, 18.8 g of lithium nitrate, 23.6 g of aluminum nitrate nonahydrate, and 72.5 g of ammonium dihydrogen phosphate were added to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus prepared was 1.5, which means it was acidic.

[0081] (2) Mixing (slurrying) 816 g of the alkaline germanium aqueous solution was taken and heated to 40° C. with stirring. The acidic lithium, aluminum, Phosphorus-containing aqueous solution Add the total amount of Ta Immediately after the addition, the aqueous solution became cloudy and a white slurry was obtained, the pH value of which was 6.7.

[0082] (3) Amorphous lithium ion conductive oxide powder Using the obtained white slurry, the same procedure as in Example 1 was carried out to obtain an amorphous lithium ion conductive oxide powder according to Example 2. The composition formula of the obtained amorphous lithium ion conductive oxide powder is Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 It was. When XRD measurement was carried out using the amorphous lithium ion conductor powder of Example 2 in the same manner as in Example 1, a halo was observed in the region of 2θ: 15° to 40°, and the half-width of the halo was 2θ: 2° or more.

[0083] The amorphous lithium ion conductor powder of Example 2 was used in the same manner as in Example 1 to obtain a lithium ion conductive oxide powder of Example 2, and further a pressed and fired body of the lithium ion conductor was obtained. Using the pressed powder sintered body of the lithium ion conductor according to Example 2, an XRD measurement was carried out in the same manner as in Example 1. As a result, it was found that the lithium ion conductive oxide powder according to Example 2 was a lithium ion conductive oxide powder having a NASICON type crystal structure (composition formula: Li 1.5 Al 0.5 Ge 1.5 P 3.0O 12 ) was found to be the case.

[0084] Example 3 (1) Preparation of raw material aqueous solution (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium dioxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0085] (II) Aqueous solution containing lithium, aluminum, and phosphorus 22.7g of lithium nitrate, 23.6g of aluminum nitrate nonahydrate, and 72.5g of ammonium dihydrogen phosphate were added to 150g of pure water to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus thus prepared was 1.4, which means it was acidic.

[0086] (2) Mixing (slurrying) 816 g of the alkaline germanium aqueous solution was taken and heated to 40° C. with stirring. The acidic lithium, aluminum, Phosphorus-containing aqueous solution Add the total amount of Ta Immediately after the addition, the aqueous solution became cloudy and a white slurry was obtained, the pH value of which was 4.1.

[0087] (3) Amorphous lithium ion conductive oxide powder Using the obtained white slurry, the same procedure as in Example 1 was carried out to obtain an amorphous lithium ion conductive oxide powder according to Example 3. The composition formula of the obtained amorphous lithium ion conductive oxide powder is Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 It was. When XRD measurement was carried out using the amorphous lithium ion conductor powder of Example 3 in the same manner as in Example 1, a halo was observed in the region of 2θ: 15° to 40°, and the half-width of the halo was 2θ: 2° or more.

[0088] The amorphous lithium ion conductor powder of Example 3 was used in the same manner as in Example 1 to obtain a lithium ion conductive oxide powder of Example 3, and further a pressed and fired body of the lithium ion conductor was obtained. Using the pressed powder sintered body of the lithium ion conductor according to Example 3, an XRD measurement was carried out in the same manner as in Example 1. As a result, it was found that the lithium ion conductive oxide powder according to Example 3 was a lithium ion conductive oxide powder having a NASICON type crystal structure (composition formula: Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 ) was found to be the case.

[0089] Example 4 (1) Preparation of raw material aqueous solution (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium dioxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0090] (II) Aqueous solution containing lithium, aluminum, and phosphorus 24.8g of lithium nitrate, 57.9g of aluminum nitrate nonahydrate, and 72.5g of ammonium dihydrogen phosphate were added to 150g of pure water to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus prepared was 1.3, which means it was acidic.

[0091] (2) Mixing (slurrying) 600 g of the alkaline germanium aqueous solution was taken and heated to 40° C. with stirring. The acidic lithium, aluminum, Phosphorus-containing aqueous solution Add the total amount of Ta Immediately after the addition, the aqueous solution became cloudy and a white slurry was obtained, the pH value of which was 3.9.

[0092] (3) Amorphous lithium ion conductive oxide powder Using the obtained white slurry, the same procedure as in Example 1 was carried out to obtain an amorphous lithium ion conductive oxide powder according to Example 4. The composition formula of the obtained amorphous lithium ion conductive oxide powder is Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 It was. When XRD measurement was carried out using the amorphous lithium ion conductor powder of Example 4 in the same manner as in Example 1, a halo was observed in the region of 2θ: 15° to 40°, and the half-width of the halo was 2θ: 2° or more.

[0093] The amorphous lithium ion conductor powder of Example 4 was used in the same manner as in Example 1 to obtain a lithium ion conductive oxide powder of Example 4, and further a pressed and sintered body of the lithium ion conductor was obtained. Using the pressed powder sintered body of the lithium ion conductor according to Example 4, an XRD measurement was carried out in the same manner as in Example 1. As a result, it was found that the lithium ion conductive oxide powder according to Example 4 was a lithium ion conductive oxide powder having a NASICON type crystal structure (composition formula: Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 ) was found to be the case.

[0094] Example 5 (1) Preparation of raw material aqueous solution (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium dioxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0095] (II) Aqueous solution containing lithium, aluminum, and phosphorus 21.7g of lithium nitrate, 39.4g of aluminum nitrate nonahydrate, and 72.5g of ammonium dihydrogen phosphate were added to 150g of pure water to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus thus prepared was 1.4, which means it was acidic.

[0096] (III) Titanium-containing aqueous solution 3.0 g of 28% ammonia water was added to 35.8 g of 35% hydrogen peroxide solution, and then 1.51 g of metatitanic acid was added and stirred until completely dissolved. The lithium, aluminum, and phosphorus-containing aqueous solution was added to the solution. The pH value at this point was 4.0.

[0097] (2) Mixing (slurrying) 684 g of the alkaline germanium aqueous solution was taken and heated to 40° C. with stirring, and the entire amount of the acidic lithium, aluminum, phosphorus, and titanium-containing aqueous solution was added thereto. Ta Immediately after the addition, the aqueous solution became cloudy and a white slurry was obtained, the pH value of which was 6.7.

[0098] (3) Amorphous lithium ion conductive oxide powder Using the obtained white slurry, the same procedure as in Example 1 was carried out to obtain an amorphous lithium ion conductive oxide powder according to Example 5. The composition formula of the obtained amorphous lithium ion conductive oxide powder is Li 1.5 Al 0.5 (Ge 1.4 Ti 0.1 )P 3.0 O 12 It was. When XRD measurement was carried out using the amorphous lithium ion conductor powder of Example 5 in the same manner as in Example 1, a halo was observed in the region of 2θ: 15° to 40°, and the half-width of the halo was 2θ: 2° or more.

[0099] (I) Oxygen Calculation The amount of oxygen associated with titanium contained in the amorphous lithium ion conductive oxide powder was calculated as follows. Since the oxide of tetravalent titanium is TiO2, the amount of oxygen related to titanium oxide is expressed by the following formula. Amount of oxygen related to titanium oxide = (Ti concentration × (formula weight of TiO2 / number of Ti atoms in TiO2) ÷ formula weight of Ti) - Ti concentration (formula) On the other hand, the ICP analysis result for titanium concentration was 0.8 mass%, Amount of oxygen related to titanium oxide = (0.8 x (79.88 / 1) ÷ 47.88) - 0.8 = 0.53 mass% It becomes.

[0100] The amorphous lithium ion conductor powder according to Example 5 was sintered at 700°C for 120 minutes to obtain a crystallized lithium ion conductor, and further a pressed and sintered body of the lithium ion conductor was obtained. The pressed and sintered body of the lithium ion conductor was subjected to XRD measurement under the conditions described in "(V) XRD measurement of amorphous lithium ion conductive oxide powder" above, and was compared with JCPDS card No. 01-080-1922. It was found that the powder was LiGePO, a lithium ion conductor with a NASICON crystal structure. 12 This confirmed that the compressed and sintered lithium ion conductive oxide powder of Example 5 was a lithium ion conductor having a NASICON type crystal structure.

[0101] Example 6 (1) Preparation of raw material aqueous solution (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium dioxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0102] (II) Aqueous solution containing lithium, aluminum, and phosphorus Add 21.7g of lithium nitrate, 39.4g of aluminum nitrate nonahydrate, and 72.5g of ammonium dihydrogen phosphate to 150g of pure water. Add An aqueous solution containing lithium, aluminum, and phosphorus was prepared. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus was 0.9, which was acidic. (2) Mixing (slurrying) 684 g of the alkaline germanium aqueous solution was taken and heated to 40° C. with stirring, and 4.1 g of zirconium oxynitrate was added and completely dissolved. The entire amount of the acidic lithium, aluminum, and phosphorus-containing aqueous solution was added thereto. Ta Immediately after the addition, the aqueous solution became cloudy and a white slurry was obtained, the pH value of which was 3.9.

[0103] (3) Amorphous lithium ion conductive oxide powder Using the obtained white slurry, the same procedure as in Example 1 was carried out to obtain an amorphous lithium ion conductive oxide powder according to Example 5. The composition formula of the obtained amorphous lithium ion conductive oxide powder is Li 1.5 Al 0.5 (Ge 1.4 Zr 0.1 )P 3.0 O 12 It was. When XRD measurement was carried out using the amorphous lithium ion conductor powder of Example 5 in the same manner as in Example 1, a halo was observed in the region of 2θ: 15° to 40°, and the half-width of the halo was 2θ: 2° or more.

[0104] (I) Oxygen Calculation The amount of oxygen associated with zirconium contained in the amorphous lithium ion conductive oxide powder was calculated as follows. Since the oxide of tetravalent zirconium is ZrO2, zirconium The amount of oxygen associated with the oxide is expressed by the following formula: Amount of oxygen related to zirconium oxide = (Zr concentration × (formula weight of ZrO2 / number of Zr atoms in ZrO2) ÷ formula weight of Zr) - Zr concentration... (formula) On the other hand, the ICP analysis result for the zirconium concentration was 1.5 mass%, Oxygen content of zirconium oxide = (1.5 x (123.22 / 1) ÷ 91.22) - 1.5 = 0.53 mass% It becomes.

[0105] The amorphous lithium ion conductor powder according to Example 6 was sintered at 700°C for 120 minutes to obtain a crystallized lithium ion conductor, and further a pressed and sintered body of the lithium ion conductor was obtained. The pressed and sintered body of the lithium ion conductor was subjected to XRD measurement under the conditions described in "(V) XRD measurement of amorphous lithium ion conductive oxide powder" above, and was compared with JCPDS card No. 01-080-1922. It was found that the powder was LiGePO, a lithium ion conductor with a NASICON crystal structure. 12 This confirmed that the compressed and sintered lithium ion conductive oxide powder of Example 6 was a lithium ion conductor having a NASICON type crystal structure.

[0106] Example 7 (1) Preparation of raw material aqueous solution (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium dioxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0107] (II) Aqueous solution containing lithium, aluminum, and phosphorus 23.9g of lithium nitrate, 39.4g of aluminum nitrate nonahydrate, and 68.9g of ammonium dihydrogen phosphate were added to 150g of pure water to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus prepared was 1.6, which means it was acidic.

[0108] (2) Mixing (slurrying) 720 g of the alkaline germanium aqueous solution was taken and LiO 11 10.2 g of Si5 solution (Sigma-Aldrich) was added. The solution was heated to 40°C while stirring, and the acid lithium, aluminum, Phosphorus-containing aqueous solution Add the total amount of Ta Immediately after the addition, the aqueous solution became cloudy, giving a white slurry.

[0109] (3) Amorphous lithium ion conductive oxide powder Using the obtained white slurry, the same procedure as in Example 1 was carried out to obtain an amorphous lithium ion conductive oxide powder according to Example 7. The composition formula of the obtained amorphous lithium ion conductive oxide powder is Li 1.5 Al 0.5 Ge 1.5 (P 2.96 S 0.04 )O 12 It was. When XRD measurement was carried out in the same manner as in Example 1 using the amorphous lithium ion conductor powder of Example 7, a halo was observed in the region of 2θ: 15° to 40°, and the half-width of the halo was 2θ: 2° or more.

[0110] (I) Oxygen Calculation The amount of oxygen associated with silicon contained in the amorphous lithium ion conductive oxide powder was calculated as follows. Since the oxide of tetravalent silicon is SiO2, the amount of oxygen related to silicon oxide is expressed by the following formula. Amount of oxygen related to silicon oxide = (Si concentration × (formula weight of SiO2 / number of Si atoms in SiO2) ÷ formula weight of Si) - Si concentration... (formula) On the other hand, the ICP analysis result for silicon concentration was 0.2 mass%, Amount of oxygen related to silicon oxide = (0.2 x (60.08 / 1) ÷ 28.09) - 0.2 = 0.23 mass% It becomes.

[0111] The amorphous lithium ion conductor powder according to Example 7 was sintered at 700°C for 120 minutes to obtain a crystallized lithium ion conductor, and further a pressed and sintered body of the lithium ion conductor was obtained. The pressed and sintered body of the lithium ion conductor was subjected to XRD measurement under the conditions described in "(V) XRD measurement of amorphous lithium ion conductive oxide powder" above, and was compared with JCPDS card No. 01-080-1922. It was found that the powder was LiGePO, a lithium ion conductor with a NASICON crystal structure. 12 This confirmed that the compressed and sintered lithium ion conductive oxide powder of Example 7 was a lithium ion conductor having a NASICON type crystal structure.

[0112] Example 8 (1) Preparation of raw material aqueous solution (I) Germanium solution 192.5 g of germanium dioxide was added to 4000 g of pure water, and the mixture was heated to 40° C. with stirring. 97.5 g of ammonia water with a concentration of 28% by mass was further added as an alkali to dissolve the germanium oxide and prepare an aqueous germanium solution. The pH value of the prepared aqueous solution was 10.7, which was alkaline.

[0113] (II) Aqueous solution containing lithium, aluminum, and phosphorus To 150g of pure water, glass 22.9 g of lithium nitrate, 39.4 g of aluminum nitrate nonahydrate, and 72.5 g of ammonium dihydrogen phosphate were added to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the aqueous solution containing lithium, aluminum, and phosphorus thus prepared was 1.8, which means it was acidic.

[0114] (2) Mixing (slurrying) 720 g of the alkaline germanium aqueous solution was taken and heated to 40° C. with stirring. The acidic lithium, aluminum, Phosphorus-containing aqueous solution Add the total amount of Ta Immediately after the addition, the aqueous solution became cloudy and a white slurry was obtained, the pH value of which was 4.5.

[0115] (3) Amorphous lithium ion conductive oxide powder Using the obtained white slurry, the same procedure as in Example 1 was carried out to obtain an amorphous lithium ion conductive oxide powder according to Example 8. The composition formula of the obtained amorphous lithium ion conductive oxide powder is Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 It was. When XRD measurement was carried out using the amorphous lithium ion conductor powder of Example 8 in the same manner as in Example 1, a halo was observed in the region of 2θ: 15° to 40°, and the half-width of the halo was 2θ: 2° or more.

[0116] The amorphous lithium ion conductor powder of Example 8 was used in the same manner as in Example 1 to obtain a lithium ion conductive oxide powder of Example 8, and further a pressed and sintered body of the lithium ion conductor was obtained. Using the pressed powder sintered body of the lithium ion conductor according to Example 8, an XRD measurement was carried out in the same manner as in Example 1. As a result, it was found that the lithium ion conductive oxide powder according to Example 8 was a lithium ion conductive oxide powder having a NASICON type crystal structure (composition formula: Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 ) was found to be the case.

[0117] Comparative Example 1 An amorphous lithium ion conductive oxide powder according to Comparative Example 1 was manufactured according to the flow diagram showing the manufacturing process of the lithium ion conductive oxide powder according to Comparative Example 1 shown in Fig. 5. Then, the manufactured lithium ion conductive oxide powder according to Comparative Example 1 was analyzed and its characteristics were evaluated.

[0118] (1) Preparation of germanium and aluminum solutions To 97.68 g of butanol, 410 g of Ge(OEt) and 33.25 g of Al(OBt) were added and dissolved to prepare a Ge, Al solution.

[0119] (2) Preparation of lithium and phosphorus solutions 2.61 g of LiCOOCH3 and 49.098 g of (NH4)2HPO4 were added to 379.64 g of pure water and dissolved to prepare a lithium-phosphorus solution.

[0120] (3) Mixing (solization) The germanium / aluminum solution and the lithium / phosphorus solution were mixed to obtain a mixed solution.

[0121] (4) Drying → Vacuum drying The mixed solution was dried in an atmosphere at 100° C., and then vacuum dried at 110° C. to obtain a powder.

[0122] (5) Firing The powder obtained by the vacuum drying was fired at 400° C. in a nitrogen atmosphere to obtain an amorphous lithium ion conductive oxide powder according to Comparative Example 1. FIG. 2 shows a 30,000-times magnified SEM photograph of the obtained amorphous lithium ion conductive oxide powder.

[0123] (6) Crushing 40 g of the amorphous lithium ion conductive oxide powder according to Comparative Example 1 was loaded into a bead mill together with 160 g of φ1 mm Zr beads and 94.32 g of IPA, and ground for 120 minutes to obtain lithium ion conductive oxide powder with adjusted particle size. (7) Drying The lithium ion conductive oxide powder with the adjusted particle size was placed in a dryer and dried at 100° C. for 3 hours, and the IPA was removed to obtain the lithium ion conductive oxide powder according to Comparative Example 1. The volume-based cumulative 50% particle diameter (D 50) was measured with Helos (dispersion pressure 5 bar) to be 1.5 μm.

[0124] (8) Composition analysis of amorphous lithium ion conductive oxide powder The amorphous lithium ion conductive oxide powder according to Comparative Example 1 was subjected to elemental analysis in the same manner as in Example 1, and the results were Li 2.40 (mass%), Al 2.94 (mass%), Ge 25.2 (mass%), and P 21.7 (mass%). The composition of each constituent element is shown in Table 2.

[0125] (9) Carbon and oxygen content analysis of amorphous lithium ion conductive oxide powder The carbon content and oxygen content in the amorphous lithium ion conductive oxide powder according to Comparative Example 1 were measured in the same manner as in Example 1, and the carbon content was 0.38 mass % and the oxygen content was 44.5 mass %. The obtained amorphous lithium ion conductive oxide powder had a Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 Furthermore, from the amounts of the metal elements, phosphorus, carbon, and oxygen described above, the amount of impurities was calculated to be 2.9 mass %. This value is shown in Table 2.

[0126] (10) BET specific surface area measurement of amorphous lithium ion conductive oxide powder The BET specific surface area of ​​the amorphous lithium ion conductive oxide powder according to Comparative Example 1 was measured in the same manner as in Example 1 and was found to be 12.3 m 2 / g. This value is shown in Table 3.

[0127] (11) XRD Measurement of Amorphous Lithium Ion Conductive Oxide Powder XRD measurement was carried out on the amorphous lithium ion conductive oxide powder according to Comparative Example 1 under the same measurement conditions as in Example 1. The obtained XRD spectrum showed a halo, as in Example 1, and it was therefore possible to confirm that the lithium ion conductor according to Comparative Example 1 was amorphous. This is shown in Table 3.

[0128] (12) Evaluation of ionic conductivity of lithium ion conducting oxide powder with NASICON type crystal structure The amorphous lithium ion conductive oxide powder of Comparative Example 1 was subjected to the same operation as in Example 1 to produce a pressed and sintered body of the lithium ion conductive oxide powder having the NASICON type crystal structure of Comparative Example 1. The ionic conductivity of the compact of the lithium ion conductive oxide powder having the NASICON type crystal structure according to Comparative Example 1 was calculated in the same manner as in Example 1, and was found to be 4.6×10 -6 The values ​​are shown in Table 3. Furthermore, the pressed powder sintered body having the NASICON type crystal structure according to Comparative Example 1 was subjected to XRD measurement in the same manner as in Example 1, and it was found to be a lithium ion conductor having the NASICON type crystal structure.

[0129] Comparative Example 2 According to the flow diagram showing the manufacturing process of the amorphous lithium ion conductive oxide powder according to Comparative Example 2 shown in FIG. 1.5 Al 0.5 Ge 1.5 (PO4)3) was produced. The lithium ion conductive oxide powder produced according to Comparative Example 2 was analyzed and its characteristics were evaluated.

[0130] (1) Weighing and mixing of ingredients As raw material powders, 2.85 g of Li2CO3, 1.31 g of Al2O3, 8.08 g of GeO2, and 17.76 g of NH4H2PO4 were weighed out. Then, the weighed raw material powders were placed in a porcelain mortar and mixed to obtain a mixed powder.

[0131] (2) Firing The resulting mixed powder was placed in an alumina crucible and fired at 400° C. for 5 hours in an air atmosphere to obtain a fired powder.

[0132] (3) Melting The resulting fired powder was placed in a platinum crucible and heated at 1200° C. for 1 hour to produce a melt.

[0133] (4) Rapid cooling The melt was rapidly cooled and vitrified to obtain a vitreous powder. FIG. 2 shows an SEM photograph of the obtained glass body at 10,000 times magnification.

[0134] (5) Crushing The obtained glass powder was roughly crushed in a mortar to obtain a powder having a particle size of 200 μm or less, and then wet-pulverized using IPA as a solvent in the same manner as in Example 1 to obtain an amorphous lithium ion conductive oxide powder with an adjusted particle size.

[0135] (6) Drying The lithium ion conductive oxide powder with the adjusted particle size was placed in a dryer and dried at 100° C. for 3 hours, and the IPA was removed to obtain an amorphous lithium ion conductive powder according to Comparative Example 2.

[0136] (7) Composition analysis of amorphous lithium ion conductive oxide powder The amorphous lithium ion conductive oxide powder according to Comparative Example 2 was subjected to elemental analysis in the same manner as in Example 1, and the results were Li 2.39 (mass%), Al 2.98 (mass%), Ge 24.5 (mass%), and P 21.8 (mass%). The composition values ​​of each constituent element are shown in Table 2.

[0137] (8) Carbon and oxygen content analysis of amorphous lithium ion conductive oxide powder The carbon content and oxygen content in the amorphous lithium ion conductive oxide powder according to Comparative Example 2 were measured in the same manner as in Example 1, and the carbon content was 0.041 mass % and the oxygen content was 44.4 mass %. The obtained amorphous lithium ion conductive oxide powder had a Li 1.5 Al 0.5 Ge 1.5 P 3.0 O 12 Furthermore, from the amounts of the metal elements, phosphorus, carbon, and oxygen described above, the amount of impurities was calculated to be 3.9 mass %. This value is shown in Table 2.

[0138] (9) BET specific surface area measurement of amorphous lithium ion conductive oxide powder The BET specific surface area of ​​the amorphous lithium ion conductive oxide powder according to Comparative Example 2 was measured in the same manner as in Example 1 and was found to be 3.3 m 2 / g. This value is shown in Table 3.

[0139] (10) XRD Measurement of Amorphous Lithium Ion Conductive Oxide Powder XRD measurement was carried out on the amorphous lithium ion conductive oxide powder according to Comparative Example 2 under the same measurement conditions as in Example 1. The obtained XRD spectrum showed a halo, as in Example 1, and it was therefore possible to confirm that the amorphous lithium ion conductor according to Comparative Example 2 was amorphous. This is shown in Table 3.

[0140] (11) Evaluation of ionic conductivity of lithium ion conducting oxide powder with NASICON type crystal structure The amorphous lithium ion conductive oxide powder according to Comparative Example 2 was subjected to the same operation as in Example 1 to produce a pressed and sintered body of the lithium ion conductive oxide powder having a NASICON type crystal structure according to Comparative Example 2. The ionic conductivity of the compact of the lithium ion conductive oxide powder having the NASICON type crystal structure according to Comparative Example 2 was calculated in the same manner as in Example 1, and was found to be 2.2 × 10 -5 The values ​​are shown in Table 3. Furthermore, the pressed powder sintered body having the NASICON type crystal structure according to Comparative Example 2 was subjected to XRD measurement in the same manner as in Example 1, and as a result, it was found to be a lithium ion conductor having the NASICON type crystal structure.

[0141] [Table 2] [Table 3] [Table 4]

Claims

1. Lithium is 0.5% by mass or more and 6.5% by mass or less, Aluminum is more than 0 mass% and 25.0 mass% or less, Germanium is more than 0 mass% and 65.0 mass% or less, Contains 10% by mass or more and 30% by mass or less of phosphorus, The specific surface area measured by the BET single point method is 15 m 2 / g or more 100m 2 / g or less.

2. Lithium, 1% by mass or more and 4% by mass or less; Aluminum, more than 0 mass% and not more than 6 mass%; 2. The amorphous lithium ion conductive oxide powder according to claim 1, containing more than 15% by mass and not more than 35% by mass of germanium.

3. 3. The amorphous lithium ion conductive oxide powder according to claim 1, further comprising 0.01% by mass or more and 0.35% by mass or less of carbon.

4. The specific surface area measured by the BET single point method is 20 m 2 / g or more 100m 2 4. The amorphous lithium ion conductive oxide powder according to claim 1, wherein the surface area of ​​the oxide is 0.1 μm or less.

5. 5. The amorphous lithium ion conductive oxide powder according to claim 1, further comprising at least one element selected from the group consisting of titanium, zirconium and hafnium.

6. 6. The amorphous lithium ion conductive oxide powder according to claim 1, further comprising 10 mass% or less of silicon.

7. The amorphous lithium ion conductive oxide powder has the general formula Li 1+x+w (Al 1-y M1 y ) x (Ge 1-z M2 z ) 2-x P 3-w S w O 12 wherein M1 is one or more selected from gallium, lanthanum, indium and yttrium, M2 is one or more selected from titanium, zirconium and hafnium, x is in the range of 0<x≦1.0, y is in the range of 0≦y≦1.0, z is in the range of 0≦z≦1.0, and w is in the range of 0≦w≦1.

0.

8. 7. The amorphous lithium ion conducting oxide powder according to claim 1, further comprising at least one element selected from the group consisting of gallium, lanthanum, indium and yttrium.

9. a slurry formation step of mixing an aqueous solution of a lithium compound, an aqueous solution of an aluminum compound, an aqueous solution of a germanium compound, and an aqueous solution of an ammonium phosphate salt to obtain a coprecipitate suspension; A step of spray-drying the slurry to obtain a dried slurry; and calcining the dried slurry at 300° C. or more and 500° C. or less.

10. 10. The method for producing an amorphous lithium ion conductive oxide powder according to claim 9, wherein in the slurry formation step, an aqueous solution of a compound containing at least one element selected from the group consisting of gallium, lanthanum, indium and yttrium is further mixed to obtain a suspension of a coprecipitate.

11. 11. The method for producing an amorphous lithium ion conductive oxide powder according to claim 9 or 10, wherein in the slurry formation step, an aqueous solution of a compound containing at least one element selected from titanium, zirconium and hafnium is further mixed to obtain a suspension of a coprecipitate.

12. 12. The method for producing an amorphous lithium ion conductive oxide powder according to claim 9, wherein in the slurry formation step, an aqueous solution of a silicon compound is further mixed to obtain a suspension of a coprecipitate.

13. 13. The method for producing an amorphous lithium ion conductive oxide powder according to claim 9, wherein the formation of the suspension in the slurry formation step is carried out by mixing an aqueous solution of the germanium compound adjusted to a pH of 8 or more.

14. A method for producing a lithium ion conductive oxide powder having a NASICON type crystal structure, comprising the step of calcining the amorphous lithium ion conductive oxide powder according to any one of claims 1 to 8 at a temperature higher than 500°C.

15. a slurry formation step of mixing an aqueous solution of a lithium compound, an aqueous solution of an aluminum compound, an aqueous solution of a germanium compound, and an aqueous solution of an ammonium phosphate salt to obtain a coprecipitate suspension; A step of spray-drying the slurry to obtain a dried slurry; and calcining the dried slurry at a temperature higher than 500°C.

Citation Information

Patent Citations

  • Method for manufacturing all-solid battery

    JP2018037341A

  • Manufacturing method of all-solid battery and all-solid battery

    JP2018101467A

  • Method for manufacturing solid electrolyte, method for manufacturing all-solid battery electrode material, and method for manufacturing all-solid battery

    JP2019046559A

  • Lithium ion secondary battery positive electrode active material, lithium ion secondary battery positive electrode, lithium ion secondary battery, and method for manufacturing said active material, said positive electrode, and said battery

    WO2015001957A1

  • Positive electrode active substance for all solid-state lithium secondary battery

    WO2019044734A1